Analisis Teori Max Weber Pada Preferensi Perilaku Konsumsi Mahasiswa di Platform E-Commerce (Perspektif Ekonomi Syariah) - Maulidayati; Muhsin Aseri; Tri Hidayati (Journal of Economic and Business Law Review, 2025)
The advancement of digital technology has transformed student consumption patterns, particularly through e-commerce platforms like Shopee and Tokopedia. This article analyzes student consumption behavior using Max Weber's social action theory and an Islamic economic perspective. Employing a qualitative, descriptive-analytical method, data were gathered through in-depth interviews with students who actively use e-commerce. The study reveals that student consumption is influenced not only by instrumental rationality but also by social, cultural, and religious values. From an Islamic economic viewpoint, some behaviors—such as excessive consumption, use of paylater services, and neglect of halal product considerations—do not align with ethical consumption principles. The findings highlight the need for increased Islamic economic literacy that extends beyond fiqh muamalah to encompass social ethics and awareness in digital transactions. Keywords: Action Theory, student consumption, e-commerce